2020
DOI: 10.3390/molecules25112630
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Crystallographic Examination of Naphthoquinone Based Diarylethene Photochromes

Abstract: Photochromic compounds have a lengthy history of study and a profusion of applications that stand to gain from these studies. Among the classes of photochromic compounds, diarylethenes show desirable properties including high fatigue resistance and thermal stability, thus meeting some of the most important criteria necessary to enter the realm of practical applications. Recently, photochromic diarylethenes containing quinone functionalities have demonstrated interesting optical and solid-state properties. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Given the differences in the structure of DAE in its solid phase and free state, [ 80 ] the self‐assembly process, which expands the application range of DAEs as a stimulus‐responsive tool, raises intermolecular interactions to an important position that should be considered. In their aggregate or solid state, DAE molecules engage in self‐assembly behavior that produces a relatively ordered nanostructure.…”
Section: Self‐assembly Models Of Daementioning
confidence: 99%
“…Given the differences in the structure of DAE in its solid phase and free state, [ 80 ] the self‐assembly process, which expands the application range of DAEs as a stimulus‐responsive tool, raises intermolecular interactions to an important position that should be considered. In their aggregate or solid state, DAE molecules engage in self‐assembly behavior that produces a relatively ordered nanostructure.…”
Section: Self‐assembly Models Of Daementioning
confidence: 99%
“…A solution of the ring-closed isomer of 2,3-bis(2,5-dimethylthiophen-3yl)-5,6-dimethyl-1,4-benzoquinone exhibited no ring-opening isomerization when left for 14 days in the dark at room temperature 34 indicating its thermal stability. In solution photochemical, ring closure of dithienyl quinone and naphthoquinone containing DAEs is known to proceed with efficiencies less 18,19,34 than that of the better known and structurally related perfluorocyclopentene containing DAEs. 35 However, chemically induced ring closure can be achieved in high yield when three equivalents of AlCl 3 in methylene chloride are added to the quinone and naphthoquinone containing ring-open isomers.…”
Section: Introductionmentioning
confidence: 99%
“…15–17 It has been demonstrated that the use of either a quinone or naphthoquinone ethene bridge allows for visible light to initiate photoisomerization in both the ring-opening and ring-closing directions. 18–20 Quinone based headgroups are also electrochemically active 21,22 and found in important biological molecules, 23,24 thus making them excellent candidates for potential therapeutic agents. 25…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation